A Study of Traditional Chinese Elements in Balinese Culture: An Acculturation Perspective - Qin Weifen (ARISTO, 2023)
Using acculturation theory to study Chinese immigrant culture from the main culture of immigrant places, this paper is presented to interpret the characteristics and reasons for Chinese elements in Balinese culture. The exchanges between China and Bali, Indonesia, have existed since ancient times, and the continuous development of the ancient Silk Road has brought the two places closer together. From 2017-to 2019, the writer went to Bali to conduct cultural field research, observed and recorded Chinese elements in Balinese society, consulted literature, and explored the embodiment of traditional Chinese cultural elements in Balinese culture. The study found that Balinese people integrate traditional Chinese culture into their daily life and work, which is reflected in some aspects of local society and culture. They absorb traditional Chinese elements into Balinese culture with a Balinese style. This produced varying degrees of influence in Balinese religion, art, literature, language, and other fields and reflected the example of cultural integration and cultural co-construction carried out by the Balinese in the face of the heterogeneous culture of Chinese culture. Chinese immigration, the homogeneity of Chinese culture and Balinese culture, the tolerance of Balinese people, and the friendship of Chinese people have created favorable conditions for Balinese culture to absorb Chinese elements